Farming with native beneficial insects : ecological pest control solutions - Lee-Mader, Eric , 1972- (Storey Publishing, 2014)
Grow bountiful organic crops while improving the biodiversity of your farm by making your land a welcoming place for native beneficial insects. Mantids, stink bugs, beetles, flies, wasps, and many others prey upon crop pests, reducing or eliminating the need for chemical pesticides. Your first step is learning to identify these important farm heroes: close-up photography and in-depth profiles familiarize you with more than 20 beneficial insects and their kin. After assessing your land, current practices, and goals, you'll find detailed instructions for a host of projects, from beetle banks to organic buffers, to improve habitat for your insect helpers.--COVER.